3D-printed surface promoting osteogenic differentiation and angiogenetic factor expression of BMSCs on Ti6Al4V implants and early osseointegration in vivo. Issue 2 (February 2019) - Zhang, Jinkai; Zhou, Wenhui; Wang, Hui; Lin, Kaili; Chen, Fengshan
Abstract: Three-dimensional-printed (3D-P) titanium implants display many advantages, such as design flexibility, higher efficiency, the capability to easily construct complex or customized structures, etc., and is believed to potentially replace traditional implants. However, the biological performance of the 3D-P titanium surface has not been investigated systematically. Herein, we analyzed the surface characteristics of 3D-P Ti6Al4V implants and evaluated the biological responses of bone marrow derived mesenchymal stromal cells (BMSCs) to the 3D-P surface in vitro . Moreover, after implantation into the rat femoral condyle for 3 and 6 weeks, the osseointegration performance was evaluated. The results showed the 3D-P Ti6Al4V implant presented distinct fluctuant macroscale rough surface and relatively better hydrophilicity which enhanced the adhesion, proliferation, osteogenic differentiation and angiogenetic factor expression of BMSCs. Moreover, the in vivo osseointegration performance was also better than that of the control group at the early stage. The present study suggested the 3D-P titanium alloy is a promising candidate to be used as implant material.